Two episodes of Paleoproterozoic metamorphosed mafic dykes in the Lvliang Complex: Implications for the evolution of the Trans-North China Orogen - Wang, X.; Zhu, W.; Ge, Rongfeng; Luo, M.; Zhu, X.; Zhang, Q.; Wang, L.; Ren, X. (Elsevier BV, 2014)
Tectonic evolution of the Trans-North China Orogen (TNCO) at ~2.2-1.8Ga is of great importance considering the prolonged controversial issue of when and how the Eastern and Western blocks were assembled to form the coherent basement of the North China Craton. We identified three types of mafic dykes in the Lvliang Complex, of which one was unmetamorphosed and two were subjected to amphibolite facies metamorphism. Zircon LA-ICP-MS U-Pb dating of six metamorphosed mafic dykes yields magmatic crystallization ages of 1919±18Ma, 1939.6±8.2Ma, 1949.9±9.6Ma, 1944±17Ma, 2116±15Ma and 2116±13Ma, indicating two major phases of mafic dykes emplacement at ~2.11Ga and ~1.94Ga, respectively. In situ zircon Hf isotope data of the ~2.11Ga samples vary in large ranges (over fifteen epsilon units) with the highest eopenHf(t) value approaching the depleted mantle array and the lowest value plotting onto the evolution line of the ~3.1Ga crust, indicating assimilation of depleted mantle-derived magma by old crustal material. For the 1.94Ga samples, almost all the eopenHf(t) values are positive with abundant data near or equal to the contemporary depleted mantle implying limited crustal assimilation. Geochemical data suggest that, most of the ~2.11Ga dykes are alkaline whereas almost all the ~1.94Ga dykes are subalkaline. The ~2.11Ga dykes show variable LREE enrichment (La/Yb=1.9-10.3), prominent Nb-Ta troughs, high Zr contents and Zr/Y ratios while the ~1.94Ga dykes display no pronounced fractionation between LREE and HREE, and also significant Nb-Ta-Ti negative anomalies, but low Zr contents and Zr/Y ratios. According to the Hf isotopic and the geochemical features, we suggest that the ~2.11Ga dykes were probably derived from a sub-continental lithospheric mantle in a continental rift with some asthenospheric contribution, whereas, the ~1.94Ga dykes were arc-related with little crustal contamination during forming and ascending process and the Nb-Ta troughs were probably attributed to subduction-related fluids and melts. Together with the previous researches of the TNCO and other parts of the North China Craton (NCC), we tend to think that there was a whole rift-subduction-collision cycle during the period of ~2.2-1.85Ga and the subduction process initiated at ~1.94Ga at least. © 2014 Elsevier B.V.